The Mechanisms Responsible for N Deficiency in Well-Watered Wheat Under Elevated CO2 - Fan, Jinjie; Halpern, Moshe; Yu, Yangliu; Zuo, Qiang; Shi, Jianchu; Fan, Yuchuan; Wu, Xun; Yermiyahu, Uri; Sheng, Jiandong; Jiang, Pingan; Ben-Gal, Alon (Frontiers in Plant Science, 2022)
Elevated CO2 concentration (e[CO2]) often promotes plant growth with a decrease in tissue N concentration. In this study, three experiments, two under hydroponic and one in well-watered soil, including various levels or patterns of CO2, humidity and N supply, were conducted on wheat (Triticum aestivum L.) to explore the mechanisms of e[CO2] induced N deficiency (ECIND). Under hydroponic conditions, N uptake remained constant even as transpiration was limited 40% by raising air relative humidity and only was reduced about 20% by supplying N during nighttime rather than daytime with a reduction of 85% in transpiration. Compared to ambient CO2 concentration, whether under hydroponic or well-watered soil conditions, as transpiration kept stable or decreased 12%, e[CO2] consistently led to more N uptake and higher biomass, while lower N concentration in aboveground organs especially leaves as long as N supply was insufficient. These results show that, due to compensation caused by active uptake, N uptake can be uncoupled from water uptake under well-watered conditions, and changes in transpiration therefore do not account for ECIND. Similar or lower tissue NO3-N concentration under e[CO2] indicated that NO3- assimilation was not limited and could therefore also be eliminated as a major cause of ECIND under our conditions. Active uptake has the potential to bridge the gap between N taken up passively and plant demand but is limited by the energy required to drive it. Compared to ambient CO2 concentration, the increase in N uptake under e[CO2] failed to match the increase of carbohydrates, leading to N dilution in plant tissues, the apparent dominant mechanism explaining ECIND. Lower N concentration in leaves rather than roots under e[CO2] validated that ECIND was at least partially also related to changes in resource allocation, apparently in order to maintain root uptake activity and prevent more serious N deficiency.